Coping Strategies For Burnout Among Middle School Female Teachers - بن يسري حورية; مزوز بركو (مجلة دراسات في سيكولوجية الانحراف, 2024)
The current study aims to reveal the level of Burnout among middle school female teachers, discovering the coping strategies most used by theme, as well as detecting whether there are differences in the level of burnout among theme due to the Length of employment. To achieve these aims, researchers used the analytical descriptive and the differentiated descriptive methodology, applied Maslach s’ Burnout Scale (MBI) and Andler & Parker Stressful Coping Strategies Scale (CISS) to a sample of middle school female teachers in the city of Ain Touta, whose ages ranged between 24 and 50 years. The data have been analyzed statistically by the spreadsheet program Excel, and the Statistical Package for Social Sciences (SPSS). The analyses reveal that there is a medium Burnout level among middle school female-teachers. It also revealed that problem-focused coping strategies are the most used by middle school teachers, followed by the emotion strategy and then the avoidance strategy and there are not statistically significant differences in Burnout level among middle school female-teachers due to Length of employment.